THE FORMATION OF UNIVERSITY STUDENTS MOTIVATION TO INDEPENDENT PHYSICAL TRAINING - Elena Kozenko; Nikolai Gordeev; Alexander Kudrya (Вестник Северо-Кавказского федерального университета, 2022)
The article discusses the formation of University student's motivation for self-employment on physical culture, which not only promotes the best mastering ofthe program and, therefore, improve physical development, and improve the health of students, but also has a positive impact on the minds of students, providing a more serious approach to the subject.